اتجاهات أولياء الأمور نحو قناة عمو يزيد - بن مبروك, هند; قداشي, نادية (جامعة الوادي - University of Eloued, 2023)
The study aimed at AmouYazid channel by raising the problem of what is the effect of parents' attitudes towards children's television programs on AmouYazid channel? In order to answer this problem and then rely on the quantitative sample and the questionnaire to collect data from the 150 members of the research community, we divided the questionnaire into 05 axes. The following sub-questions were addressed: • What are the motives for children watching the program of AmoYazid? • What is the parents' assessment of the impact of AmoYazid TV programs? And we reached the following results: • The vast majority of viewers watch Ammo Yazid channel, making it very popular among children for the purpose of entertainment, entertainment, knowledge and information. • Parents' preference for AmouYazid channel and its programmes • Follow-up of the children in the channel in the evening due to their free time and their love for the channel. • Parents' evaluation of the channel as a useful tool that played an effective and important role in raising their children, entertaining them, and acquiring knowledge and information.
مذكرة ماستر إعلام وإتصال
Keywords: children’s tvprogrammes, uncle Yazid s channel ,parent directions. .; برامج الأطفال التلفزيونية , قناة عمو يزيد , إتجاهات الوالدين